Technical Evaluation of Road Infrastructure Bridges in the Department of Antioquia - Garcia, John Mario; Ospina Giraldo, Jaime; Graciano, Edir Amparo (Ingeniería Solidaria, 2014)
The economic and social development of a region is directly related to the condition of its road infrastructure. The lack of a bridge generates total interruption in the traffic of goods over its surface, generating incalculable material and social losses until vehicular flow is restored. The Department of Antioquia has one of Colombia’s most extensive road networks. The departmental government is responsible for proper functioning of the secondary road network in Antioquia. This includes preventive maintenance of all of its bridges, but unfortunately a significant percentage has not been properly maintained since construction, facilitating the appearance of structural faults and even possible collapse. This research, carried out between 2008 and 2012, identified the physical and structural conditions of each bridge in the secondary road network of the Department of Antioquia, 11% of which  require immediate intervention because of the level of damage found while 48% are functioning properly.
Keywords: department of Antioquia; bridges; road infrastructure